2010
DOI: 10.1055/s-0030-1262316
|View full text |Cite
|
Sign up to set email alerts
|

Does Rhinoplasty Improve Nasal Breathing?

Abstract: Rhinoplasty is a surgical procedure that aims to improve nasal aesthetics and nasal breathing. The aesthetic improvement of the nose is usually judged subjectively by the patient and the surgeon, but the degree of improvement of nasal obstruction is difficult to assess by clinical examination only. The measurement of peak nasal inspiratory flow (PNIF) is a reliable tool that has been shown to correlate with other objective methods of assessing nasal breathing and with patients' symptoms of nasal obstruction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Nevertheless, these findings suggest that rhinoplasty, by using and combining several remodelling techniques to reshape the nasal pyramid and bring the shape of the nose close to the "ideal" nasal pyramid, is able to improve nasal airflow. These findings are consistent with other studies that have found rhinoplasty to improve nasal breathing (22)(23)(24)(25) . Most studies that have evaluated nasal airway obstruction after nasal surgery using patient-reported nasal obstruction scores, such as the NOSE scale or VAS, have also found statistically significant improvement of nasal obstruction after surgery (22,24,26) .…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, these findings suggest that rhinoplasty, by using and combining several remodelling techniques to reshape the nasal pyramid and bring the shape of the nose close to the "ideal" nasal pyramid, is able to improve nasal airflow. These findings are consistent with other studies that have found rhinoplasty to improve nasal breathing (22)(23)(24)(25) . Most studies that have evaluated nasal airway obstruction after nasal surgery using patient-reported nasal obstruction scores, such as the NOSE scale or VAS, have also found statistically significant improvement of nasal obstruction after surgery (22,24,26) .…”
Section: Discussionsupporting
confidence: 93%
“…The improvement in function was measured in this study using NOSE scale as a validated subjective tool, and PNIF as an objective one. Similar to other studies using these two tools, 21,23,[32][33][34][35] the current study has shown a highly significant improvement in function. Interestingly, even the group of patients who developed saddle deformity had a significant improvement in their function subjectively and objectively.…”
Section: Discussionsupporting
confidence: 88%
“…No correlation was, however, performed. Xavier in their study of twenty‐three consecutive patients undergoing rhinoplasty showed an improvement in NIPF values in all but three patients after surgery. They found the greatest improvement in NIPF was achieved when bilateral spreader grafts were used, a subgrouping we did not perform in our study.…”
Section: Discussionmentioning
confidence: 94%